The Influence of Leadership Style, Work Motivation, and Work Environment on the Performance of Aircraft Maintenance Personnel (Human Resource Management Literature Review) - Hasanudin (Dinasti International Journal of Digital Business Management, 2025)
The purpose of this study is to develop hypotheses regarding the influence of leadership style, work motivation, and work environment on the performance of aircraft maintenance personnel, which will be used in future research in the field of human resource management. This study employs a library research method, sourcing data from previous studies obtained through academic platforms such as Google Scholar, Publish or Perish, and other academic databases. The findings of this study indicate that: 1) Leadership style influences the performance of aircraft maintenance personnel; 2) Work motivation influences the performance of aircraft maintenance personnel; and 3) Work environment influences the performance of aircraft maintenance personnel.